Evidence from Keewatin (Central Nunavut) for Paleo-Ice Divide Migration - McMartin, Isabelle; Henderson, Penny (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractIce directional indicators were compiled from extensive field mapping and air-photo interpretation in the Keewatin region of central Nunavut. The profusion of multi-faceted bedrock outcrops, intersecting striations, superimposed streamlined landforms, and stacked till units, particularly beneath the former Keewatin Ice Divide, is interpreted to be the result of the migration of the main ice divide in the region, by as much as 500 km between ice-flow phases, possibly through much of the Wisconsinan glaciation. This palimpsest glacial landscape reflects protection under an ice divide because of low-velocity basal sliding, and changes in flow velocity as a result of shifting ice flow centres. Relative ages of regional ice-flow sets were used to reconstruct multiple phases of paleo-ice flows, stemming from ice centres external to the region prior to or at LGM, and from a local ice divide throughout deglaciation. This work refutes previous interpretations of the age and stability of the Keewatin Ice Divide, and has implications for interpreting glacial dispersal trains and for mineral exploration in Keewatin.